ZNF307 (Zinc Finger Protein 307) Acts as a Negative Regulator of Pressure Overload–Induced Cardiac Hypertrophy. Issue 4 (April 2017) - Yu, Chang-Jiang; Liang, Chen; Li, Yu-Xia; Hu, Qing-Qing; Zheng, Wei-Wan; Niu, Na; Yang, Xu; Wang, Zi-Rui; Yu, Xiao-Di; Zhang, Bao-Long; Song, Bin-Lin; Zhang, Zhi-Ren
Abstract : Pathological cardiac hypertrophy is a key risk factor for heart failure. We found that the protein expression levels of the ZNF307 (zinc finger protein 307) were significantly increased in heart samples from both human patients with dilated cardiomyopathy and mice subjected to aortic banding. Therefore, we aimed to elucidate the role of ZNF307 in the development of cardiac hypertrophy and to explore the signal transduction events that mediate the effect of ZNF307 on cardiac hypertrophy, using cardiac-specific ZNF307 transgenic (ZNF307-TG) mice and ZNF307 global knockout (ZNF307-KO) mice. The results showed that the deletion of ZNF307 potentiated aortic banding–induced pathological cardiac hypertrophy, fibrosis, and cardiac dysfunction; however, the aortic banding–induced cardiac hypertrophic phenotype was dramatically diminished by ZNF307 overexpression in mouse heart. Mechanistically, the antihypertrophic effects mediated by ZNF307 in response to pathological stimuli were associated with the direct inactivation of NF-κB (nuclear factor-κB) signaling and blockade of the nuclear translocation of NF-κB subunit p65. Furthermore, the overexpression of a degradation-resistant mutant of IκBα (IκBα S32A/S36A ) reversed the exacerbation of cardiac hypertrophy, fibrosis, and dysfunction shown in aortic banding–treated ZNF307-KO mice. In conclusion, our findings demonstrate that ZNF307 ameliorates pressure overload–induced cardiac hypertrophy by inhibiting the activity of NF-κB–signaling pathway. Abstract : Supplemental Digital Content is available in the text.